Usaha meminimalkan cacat produk untuk merencanakan persediaan bahan baku yang optimal (Studi kasus: UD XYZ) - Romadhon, Muhammad Guntur; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study uses quantitative methods and aims to provide inventory control proposals using forecasting analysis and continuous review systems and to find out the root cause of the gallon cap product defects at UD XYZ. The results obtained are obtaining the procurement cost of Aqua HDPE Plastic, which has savings of Rp9,187,465.00. For the procurement cost of Dark Blue HDPE Plastic, there is a savings of Rp6,770,828.50. For the procurement cost of Dark Blue HDPE Plastic, there is a savings of Rp14,079,792.00. For the procurement cost of Light Blue HDPE Plastic, there is a savings of Rp16,365,627.50. For the procurement cost of White HDPE Plastic, there is a savings of Rp36,853,183.50. For the procurement cost of Light Blue HDPE Plastic, there is a savings of Rp26,275,091.00. It can be seen that the total inventory cost using the continuous review method is considered more efficient and can also have safety stock and reorder points.